The Thermal Regime, including a Reversed Thermal Offset, of Arid Permafrost Sites with Variations in Vegetation Cover Density, Wudaoliang Basin, Qinghai‐Tibet Plateau. (17th March 2015) - Lin, Z.; Burn, C. R.; Niu, F.; Luo, J.; Liu, M.; Yin, G.
Abstract Commonly, permafrost conditions are characterised by one or two temperature profiles within each unit of a study area. Intra‐unit variation is therefore unknown, and the extent to which the data represent unit conditions cannot be estimated. We have collected ground temperatures from 55 boreholes to 5 m depth drilled in four 200 m2 plots next to the Qinghai‐Tibet Railway near the town of Wudaoliang. The sites are in a dry area of active aeolian erosion and straddle an alpine meadow ecotone between well‐ and sparsely vegetated ground cover. The annual mean air temperature at Wudaoliang is currently about ‐4°C. There is pronounced asymmetry in the seasonal distribution of precipitation, with very little falling between October and April, so that there is almost no snow cover in winter. At every site, air and ground surface temperatures were similar in winter, but the ground surface was considerably warmer than the air in summer in the radiation‐rich environment of the Qinghai‐Tibet Plateau. Thawing season n‐factors were between 2 and 3 as a result. Ground conditions in the well‐vegetated meadows were in thermal equilibrium with surface conditions, with the annual mean temperature near the permafrost table (Tps) between ‐1.2 and ‐1.9°C. Within plot spatial variability for Tps, estimated from the standard error of the replicate measurements, was ∼ 0.05°C at each site. Thermal conditions in the eroded, sparsely vegetated area appeared to be transient and warming, with current Tps of ‐0.5°C. The driest site showed a reversed thermal offset in the uppermost active layer. We hypothesise that the reversed offset may occur due to extremely dry conditions in winter, so that at the ground surface, the thermal conductivity is lower in winter than under the moist conditions of summer. Copyright © 2015 John Wiley & Sons, Ltd.